2019
DOI: 10.1136/oemed-2018-105336
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and cancer incidence among female Australian firefighters

Abstract: ObjectivesTo investigate the mortality and cancer incidence of female firefighters, a group where there are limited published findings.MethodsParticipating fire agencies supplied records of individual firefighters including the number and type of incidents attended. The cohort was linked to the Australian National Death Index and Australian Cancer Database. Standardised mortality ratios and standardised cancer incidence ratios were calculated separately for paid and volunteer firefighters. Volunteer firefighte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 19 publications
2
18
0
Order By: Relevance
“…As this study features a set of 256 cases of cancer or preinvasive cancer reported by female firefighters, the question arises as to what types of cancers have been disclosed and how the frequency, biological nature, and clinical characteristics of these cancers compare to those experienced among women in the general public. Similar to other accounts ( 9 , 11 , 12 , 28 ), this study observed a wide variety of different types of cancers. In order of descending frequency, these were comprised of breast, cervical, melanoma, skin, uterine, colorectal, thyroid, and ovarian cancer, among others.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As this study features a set of 256 cases of cancer or preinvasive cancer reported by female firefighters, the question arises as to what types of cancers have been disclosed and how the frequency, biological nature, and clinical characteristics of these cancers compare to those experienced among women in the general public. Similar to other accounts ( 9 , 11 , 12 , 28 ), this study observed a wide variety of different types of cancers. In order of descending frequency, these were comprised of breast, cervical, melanoma, skin, uterine, colorectal, thyroid, and ovarian cancer, among others.…”
Section: Discussionsupporting
confidence: 90%
“…Cancer mechanism-wise, the skin is the largest organ of the body, is a very metabolically active tissue, and covers a wide surface area. As fire-generated carcinogens penetrate bunker gear and are absorbed into hot, moist skin, this would provide, in contrast to solar-derived ultraviolet exposure, a rationale for the higher melanoma rates consistently reported among firefighters ( 8 , 11 , 12 , 46 ). Fortunately, the melanoma cases in this study did not appear to be more aggressive than those observed in the public.…”
Section: Discussionmentioning
confidence: 99%
“…In line with our results, increased risks of some respiratory system, digestive tract, skin, and male reproductive cancers were reported in firefighters, but some protective associations were also observed, which again may be due to the healthy volunteer effect [49][50][51][52][53][54]. Consistent with previous studies, lung cancer was not observed to have a higher mortality risk associated with wildfire-related PM 2.5 exposure, while statistically significant associations were observed in female and older populations with non-wildfire PM 2.5 in the current study [46][47][48][49][50][51][52][53][54]. However, our previous study conducted in the same population and over a similar study period showed significant associations between all-source PM 2.5 and lung cancer mortality for all subgroups (both sexes and age groups) [55].…”
Section: Plos Medicinesupporting
confidence: 85%
“…The American Cancer Society (ACS) Cancer Prevention Study II demonstrated that wildland firefighters have an increased risk of lung cancer mortality [45]. Studies from Australia AU : Pleasecheckthattheeditstothesentence}Stu showed possible increased risks of colorectal and prostate cancers in paid male wildfire firefighters, colorectal and kidney cancer in male firefighters, and all malignancies in female wildfire firefighters [46][47][48]. However, no increased cancer mortality risks were observed, which may be due to the "healthy volunteer" effect [46][47][48].…”
Section: Plos Medicinementioning
confidence: 99%
See 1 more Smart Citation